2017
DOI: 10.1002/mgg3.273
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence, penetrance, and expressivity of etiologicIRF6variants in orofacial clefts patients from sub‐Saharan Africa

Abstract: BackgroundOrofacial clefts are congenital malformations of the orofacial region, with a global incidence of one per 700 live births. Interferon Regulatory Factor 6 (IRF6) (OMIM:607199) gene has been associated with the etiology of both syndromic and nonsyndromic orofacial clefts. The aim of this study was to show evidence of potentially pathogenic variants in IRF6 in orofacial clefts cohorts from Africa.MethodsWe carried out Sanger Sequencing on DNA from 184 patients with nonsyndromic orofacial clefts and 80 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 27 publications
0
12
0
1
Order By: Relevance
“…Several previous studies had screened for IRF6 PV in patients with nonsyndromic OFC, with the goal of identifying their frequency and any related clinical characteristics. These studies found that patients with VWS accounted for 0% to 3.7% of OFC cases initially cataloged as nonsyndromic forms (Zucchero et al, 2004; Birnbaum et al, 2008; Pegelow et al, 2008; Jehee et al, 2009; Desmyter et al, 2010; Larrabee et al, 2011; Salahshourifar et al, 2012; Wu-Chou et al, 2013; Khandelwal et al, 2016; Leslie et al, 2016; Gowans et al, 2017). A posteriori clinical evaluation suggested that there was minimal expression of lower lip pits in 31.8% of the patients with IRF6 PV (7 of 22 with information available).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several previous studies had screened for IRF6 PV in patients with nonsyndromic OFC, with the goal of identifying their frequency and any related clinical characteristics. These studies found that patients with VWS accounted for 0% to 3.7% of OFC cases initially cataloged as nonsyndromic forms (Zucchero et al, 2004; Birnbaum et al, 2008; Pegelow et al, 2008; Jehee et al, 2009; Desmyter et al, 2010; Larrabee et al, 2011; Salahshourifar et al, 2012; Wu-Chou et al, 2013; Khandelwal et al, 2016; Leslie et al, 2016; Gowans et al, 2017). A posteriori clinical evaluation suggested that there was minimal expression of lower lip pits in 31.8% of the patients with IRF6 PV (7 of 22 with information available).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous groups have screened the IRF6 gene for PV in patients with an OFC to determine the proportion of patients with VWS that have been erroneously classified with a nonsyndromic form. Indeed, PV in IRF6 have been identified in 0% to 3.7% of patients with an OFC (Zucchero et al, 2004; Birnbaum et al, 2008; Pegelow et al, 2008; Jehee et al, 2009; Desmyter et al, 2010; Larrabee et al, 2011; Salahshourifar et al, 2012; Wu-Chou et al, 2013; Khandelwal et al, 2016; Leslie et al, 2016; Gowans et al, 2017). A posteriori clinical evaluation of patients in which an IRF6 PV was identified revealed that around 31% of these patients showed a minimal expression of lip pits and 50% had a first-degree relative with mixed OFC.…”
Section: Introductionmentioning
confidence: 99%
“…OFCs have multifactorial etiology, with genetic, stochastic, environmental, and gene‐environment factors playing crucial roles (Dixon et al, 2011). Various studies have demonstrated that both syndromic and nonsyndromic forms of OFCs may exhibit variable penetrance and expressivity, with molecular genetic mechanisms such as compound heterozygosity and gene‐gene interactions being suggested as possible underlying mechanisms (Dixon et al, 2011; Gowans et al, 2017). Moreover, genes for syndromic cases, such as IRF6 (OMIM:607199), have been implicated in the etiology of nonsyndromic cases (Kondo et al, 2002; Zucchero et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The Interferon Regulatory Factor 6 gene has been associated with syndromic and nonsyndromic orofacial clefts. Gowans LJ et al [4] carried out Sanger Sequencing on DNA from184 patients with nonsyndromic orofacial clefts and 80 individuals with multiple congenital anomalies that presented with orofacial clefts. They sequenced all the nine exons of IRF6 as well as the 5' and 3' untranslated regions.…”
mentioning
confidence: 99%
“…In Africa population, prevalent of the porofacial clefts with variable penetrance and expressivity is induced by IRF6 mutants. Their observations are relevant for detection of high-risk families as well as genetic counseling [4]. The etiology of nonsyndromic cleft palate remains elusive, but it has been suggested that causative genes of syndromic CL/P might also contribute to NSCL/P.…”
mentioning
confidence: 99%